Ginkgetin inhibits proliferation of HeLa cells via activation of p38/NF-ÎºB pathway - Cheng, Jianxia; Li, Yun; Kong, Jianping (Cellular and Molecular Biology, 2019)
Effect of ginkgetin on proliferation of human cervical cancer (HeLa) cells and the underlying mechanism were investigated. Human cervical cancer (HeLa) cells were cultured at 37 °C in 10 % fetal bovine serum (FBS) supplemented RPMI 1640 medium in a humidified incubator containing 5 % CO2. Cell proliferation was determined using MTT assay, while real-time quantitative polymerase chain reaction (qRT-PCR) and enzyme-linked immunosorbent assay (ELISA) were used to determine the levels of expression of interleukin 1Î² (IL-1Î²), tumor necrosis factor-Î± (TNF-Î±) and interleukin 8 (IL-8). The expressions of p38 mitogen-activated protein kinases (p38 MAPK) and nuclear factor kappa-light-chain-enhancer of activated B cells (NF- ÎºB) were determined using Western blotting. Treatment of HeLa cells with ginkgetin significantly and time- and dose-dependently inhibited their proliferation (p < 0.05). The invasion of the cells were also significantly and dose-dependently decreased, when compared with control cells (p < 0.05). The expressions of p-p38 and p-NF-ÎºB were significantly and dose-dependently down-regulated, relative to control group (p < 0.05). However, the expressions of p38 and NF-ÎºB in ginkgetin-treated cells were not significantly different from those of control group (p > 0.05). The results of qRT-PCR and ELISA showed that the levels of expression of TNF-Î±, IL-1Î² and IL-8 mRNAs were significantly and dose-dependently reduced in HeLa cells after 48 h of treatment with ginkgetin, when compared with the control group (p < 0.05). The anti-proliferative effect of ginkgetin on HeLa cells is exerted via a mechanism involving the p38/NF-ÎºB pathway.